What do deficits tell us about debt? Empirical evidence on creative accounting with fiscal rules in the EU - Jürgen von Hagen; Guntram B. Wolff (Deutsche Bundesbank, 2004)
Fiscal rules, such as the excessive deficit procedure and the stability and growth pact (SGP), aim at constraining government behavior. Milesi-Ferretti (2003) develops a model in which governments circumvent such rules by reverting to creative accounting. The amount of this creative accounting depends on the reputation cost for the government and the economic cost of sticking to the rule. In this paper, we provide empirical evidence of creative accounting in the European Union. We find that the SGP rules have induced governments to use stock-flow adjustments, a form of creative accounting, to hide deficits. This tendency to substitute stock-flow adjustments for budget deficits is especially strong for the cyclical component of the deficit, as in times of recession the cost of reducing the deficit is particularly large.
Keywords: H62; H70; H61; E62; H63; 330; Fiscal rules; stock-flow adjustments; debt-deficit adjustments; stability and growth pact; excessive deficit procedure; ESA 95; EU-Stabilitätspakt; Finanzpolitik; Konvergenzkriterien; Öffentliche Finanzkontrolle; Öffentliches Rechnungswesen; Öffentliche Schulden; EU-Staaten